Towards Better Health in Sub-Saharan Africa - Shaw, R. Paul; Elmendorf, Edward (World Bank, Washington, DC, 2012)
This article reports on a vision of health improvement that challenges African countries and their external partners to rethink current health strategies. The report stresses positive experiences in sub-Saharan Africa and concludes that far greater progress in improving health is possible than has been achieved in the past - even within existing resource constraints. On the basis of experience with well functioning health care systems in a number of countries, the report proposes that a basic set of health services can be provided in low-income Africa at an annual cost of $13 per person. This report illustrates the costs and benefits involved, casting new light on the advantages of health reform.